A consecutive series of patients undergoing trans-urethral cystolithotripsy with ballistic lithotripsy by a tertiary referral center for neurogenic bladder - Maltagliati, Matteo; Sampogna, Gianluca; Citeri, Marco; Guerrer, Chiara Stefania; Zanollo, Lucia Giovanna; Rizzato, Luigi; Montanari, Emanuele; Micali, Salvatore; Rocco, Bernardo; Spinelli, Michele (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work Patients with neurogenic bladder (NB) have an increased risk of developing bladder stones due to bladder catheter, incomplete bladder emptying, recurrent urinary tract infections, and immobilization. In these patients, minimally invasive treatments are usually adopted, as noninvasive extracorporeal shockwave lithotripsy is limited by the risk of not clearing all stone fragments, and open surgery is usually discouraged. The aim of our study was to present our experience with trans-urethral cystolithotripsy (TUCL) in patients treated by a tertiary referral center for NB. Methods We retrospectively collected pre-, intra- and post-operative data from our patients, who underwent TUCL from October 2013 to October 2019. The procedure was performed with a 24 Fr cystoscope and a ballistic lithotripter. Lapaxy was performed with Ellik bladder evacuator. All procedures were performed by two expert surgeons. Stone-free rate (SFR) was defined as the percentage of patients with absence of residual fragments > 2 mm in diameter. Results We performed consecutively 90 TUCLs in 75 patients during the selected period. SFR was 94.1%. Intra- and post-operative complications occurred in one (1.1%) patient. Our statistical analysis outlined the SFR was affected in a statistically significant way by sex, NB etiology, stone cumulative diameter, and operative time. Conclusion Our series proved the safety and efficacy of TUCL with ballistic lithotripsy in NB patients. Further multicenter randomized controlled trials are mandatory to validate definitively TUCL as the gold standard therapy for bladder urolithiasis in NB patients, and to identify risk factors limiting the SFR.